Peran Guru dan Lingkungan Sekolah dalam Membentuk Karakter Anak di SMK Hang Nadim Batam - Siagian, Mauli; Wasiman, Wasiman; Sitorus, David Humala (ASOSIASI IDEBAHASA KEPRI, 2025)
Hang Nadim Batam Vocational School is one of the vocational schools that has a fairly good reputation in Batu Aji Batam, so because of this it has become a reference for people in the surrounding area to send their children to school. The strategic location and affordable costs are considerations made by parents when sending their children to Hang Nadim Vocational School. Some of the majors available at the school include Accounting, Electrical Engineering and Automotive, which are majors that are in great demand by prospective students. Community service carried out by a team of Putera Batam University lecturers aims to share knowledge with the community/school, which is one form of the Tri Dharma of Higher Education. The current theme of service is the role of teachers and school culture in forming superior students at Hang Nadim Vocational School, Batam, which is an analysis and the results of a survey conducted by the service team at Hang Nadim Vocational School, Batam. The results of the service carried out can be concluded, namely: 1) The role of teachers is very important in educating superior students who have character so that students can have skills and competencies that can compete in society. 2) A good school environment that supports student activities can provide superior student growth and be responsible for the tasks and obligations given by the teachers. School culture can shape the character of students who are able and adapt quickly by sharing a more flexible environment so as to provide students with comfort in completing their studies.